INTERPROFESSIONAL COLLABORATION BETWEEN NURSES AND HEALTH ASSISTANTS: ENHANCING PATIENT CARE QUALITY AND SAFETY IN SAUDI ARABIAN HEALTHCARE SETTINGS - Saad Dhaher Aqeel M. Al Dhafeeri, Nawaf Sayer Abdulrahman S. Aljohan, Noura Khaled Khalifa A. Al-Thawab, Mohammed Atshan Ghuaim M. Alhusaini, Hmoud G Hali Aqeel H. Al Dhafeeri, Nawaf Ngheimesh Aqeel N. Al-Dhafiri, (Chelonian Research Foundation, 2022)
Background: Interprofessional collaboration (IPC) between nurses and health assistants is crucial for delivering high-quality and safe patient care. However, limited research has explored the current state of IPC in Saudi Arabian healthcare settings and its impact on patient outcomes. This study aimed to investigate the perceptions and experiences of nurses and health assistants regarding IPC and its role in enhancing patient care quality and safety in Saudi Arabia. Methods: A mixed-methods approach was employed, involving a cross-sectional survey and semi-structured interviews. A total of 248 nurses and 156 health assistants from three tertiary hospitals in Riyadh, Saudi Arabia, participated in the survey. The survey assessed participants' perceptions of IPC using the Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration (JSAPNC) and the Safety Attitudes Questionnaire (SAQ). Semi-structured interviews were conducted with 20 nurses and 15 health assistants to explore their experiences and perspectives on IPC. Results: The survey results revealed generally positive attitudes towards IPC among both nurses and health assistants. However, nurses reported significantly higher scores on the JSAPNC compared to health assistants (p < 0.05). The SAQ scores indicated that both groups perceived teamwork climate and safety climate positively, but nurses scored higher on these domains than health assistants (p < 0.01). Thematic analysis of the interviews identified four main themes: (1) the importance of IPC in patient care, (2) barriers to effective IPC, (3) facilitators of IPC, and (4) strategies to enhance IPC. Conclusion: This study highlights the importance of IPC between nurses and health assistants in promoting patient care quality and safety in Saudi Arabian healthcare settings. While both groups demonstrated positive attitudes towards IPC, nurses reported higher levels of collaboration and perceived safety climate compared to health assistants. The findings suggest a need for targeted interventions to improve IPC, such as interprofessional education, clear role delineation, and supportive organizational policies. Implementing these strategies may contribute to better patient outcomes and a stronger culture of safety in Saudi Arabian healthcare facilities. Keywords: interprofessional collaboration, nurses, health assistants, patient care quality, patient safety, mixed-methods, Saudi Arabia